Management of contralateral molar teeth with necrotic pulp and open apexes using platelet‐rich plasma and vital pulp therapy - Mostafa Ghandi; Farnaz Ghorbani; Parisa Sanaei‐Rad (Clinical Case Reports, 2023)
Key Clinical Message Regenerative endodontics holds promising potential for the regeneration of living tissues in teeth with necrotic pulp and periapical lesion. Platelet‐rich plasma can be easily prepared and used as an ideal scaffold for pulp regeneration.